Sustaining progress the ideal coop way Police Regional Office 11 Multi-Purpose Cooperative onward toward 2010 - Costelo Almalyn N. (School of Management, University of the Philippines Mindanao, 2006)
This paper is written with Police Regional Office 11 Multi-purpose Cooperative in mind. It uses sound business principles and strategies generally practiced and recommended by successful business managers. For this reason, the reader may use this paper an the principles and strategies herein applied as a reference for his/her work with organizations facing similar condition as the coop. Chapter 1 serves as the introductory part of the whole paper. It provides the company background, purpose and significance of the study, the scope and purpose as well as the limitation of the study. It also discloses the strategic framework to be utilized in the analysis and recommendation which is adopted by the author from Fred David. Chapter 2 focuses on the environmental factors that directly affect the cooperative. The evaluation on the environmental factors yielded the following as opportunities: a) positive economic outlook; b) globalization; c) favorable regulations; d) Landbank financial assistance to the cooperative; e) PNP?s continued recruitment; f) stable bank interest rate; and, g) the fact that PNP personnel are spread out in the provinces. The following threats were also revealed, namely: a) continued inflation of prices; b) political crisis; c) PNP salary are coursed through Automated Teller Machines (ATM); d) the existence of new coops in the provinces; e) massive brain drain; and f) possible discontinuance of automatic salary deduction. Chapter 3 discusses the different aspects of the coop including its management, human resource, marketing, operation, and finance. The analysis made resulted to the identification of the Cooperative?s strengths and weaknesses. The following strengths are identified: a) profitable operation; b) loyal customers; c) permanent employees; d) collection efficiency; e) increase in membership; and f) availability of loan facility with Land Bank of the Philippines. On the other hand, the following are the weaknesses: a) low human relations performance; b) limited membership/market; c) unpredictable assignment of members; d) few personnel trainings; e) membership withdrawals. Chapter 4 articulates the mission, vision and goals of the cooperative vis-à-vis the cooperative pledge. Chapter 5 examines the long-range objectives of the coop to provide a basis for direction and evaluation. This chapter also unfolds the generic and grand strategies that the author suggests for the cooperative to pursue. The author proposes market penetration and market development. Chapter 6 provides for the Key Result Areas (KRAs) and their corresponding Performance Indicators (PIs).